Growth performance and stress response of serukan juvenile (Osteochilus sp) in different salinity media - Samuki, Khairul; Diana, Farah; Islama, Dini; Hendri, Afrizal; Hasibuan, M Barru Airil Fizra; Yusdi, Aris; Saputra, Fazril (Acta Aquatica: Aquatic Sciences Journal, 2023)
Serukan fish (Osteochilus sp) has potential as a cultivation commodity with economic value. Environmental engineering, such as the manipulation of salinity media, has succeeded in increasing the growth of freshwater fish. However, there is no information about the optimal salinity setting for raising serukan fish. This study aims to determine the optimal media salinity based on the growth performance of the serukan juvenile. This study used a completely randomized design (RAL) with four treatments and three replications. The maintenance media in this study included control, P1 (3 ppt), P2 (6 ppt) and P3 (9 ppt). The study was conducted for 45 days with commercial feed. The test parameters included feed chemical analysis, blood glucose, SGR, FI, FE and SR. Data were analyzed by ANOVA and Duncan's further test. The optimal concentration of media salinity is determined by an orthogonal polynomial test. The results showed that the salinity-rearing media had a significant effect on the specific growth rate (SGR) and the efficiency of feed usage. The optimal concentration of salinity was found at 3.8 ppt, indicating that the fish call tends to achieve optimal growth at this salinity. The physiological response (stress) of fish, as measured by blood glucose levels, is also directly proportional to the level of salinity and growth performance.Keywords: Blood glucose; Growth performance; Media manipulation; Osteochilus sp; Stress response.